Chapter 4: Djinanginy may may – Other work - Buchanan, J.; Collard, Len; Cumming, Ingrid; Palmer, D.; Scott, Kim; Hartley, John (Cultural Science, 2016)
This chapter offers a comparative framework for thinking about and understanding the Noongarpedia project. In particular, work in neighbouring fields helps us better to understand the complex relationship between Noongar and non-Noongar knowledge as it is shared and mediated by those involved in the Noongarpedia project. This body of work offers new ways of understanding how Noongar people and others may support a ‘Noongar knowledge network’. Rather than representing new forms of information and communication technology (ICT) as merely a threat to Indigenous knowledge and cultural forms, this work recognises that many Indigenous groups are embracing ITC. The adoption of new platforms (such as Facebook, GIS, Garageband etc.) has seen distinctly Indigenous forms of production being taken on by Indigenous groups. Our project links with others that engage with the possibilities that may emerge from digital media to support Indigenous cultural maintenance, reformation and transmission. A distinct approach to ‘media citizenship’ in the digital era, based on the activism of citizens themselves using new media affordances (Hartley et al. 2013), focuses on a ‘bottom-up’ process of knowledge-sharing. In this context, Wikipedia may be seen to provide not only a technological means to record ‘knowledge artefacts’ of the past, but also a social means to activate Noongar and others in the performance of that culture as future-facing civic action.